2013
DOI: 10.3174/ajnr.a3502
|View full text |Cite
|
Sign up to set email alerts
|

Association of CT Perfusion Parameters with Hemorrhagic Transformation in Acute Ischemic Stroke

Abstract: BACKGROUND AND PURPOSE:Prediction of hemorrhagic transformation in acute ischemic stroke could help determine treatment and prognostication. With increasing numbers of patients with acute ischemic stroke undergoing multimodal CT imaging, we examined whether CT perfusion could predict hemorrhagic transformation in acute ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 41 publications
4
49
0
Order By: Relevance
“…The maximum AUC for predicting HT found in our study was relatively low at 0.77, but was within the range of the results of other multivariate analyses in studies investigating predictors of HT with CTP (range 0.69–0.92) [13, 16, 17, 19, 31]. We did find a significant relation between CBV deficit and BBBP, and the occurrence of HT in univariate analysis, but this could not be confirmed in our multivariate analysis.…”
Section: Discussionsupporting
confidence: 54%
“…The maximum AUC for predicting HT found in our study was relatively low at 0.77, but was within the range of the results of other multivariate analyses in studies investigating predictors of HT with CTP (range 0.69–0.92) [13, 16, 17, 19, 31]. We did find a significant relation between CBV deficit and BBBP, and the occurrence of HT in univariate analysis, but this could not be confirmed in our multivariate analysis.…”
Section: Discussionsupporting
confidence: 54%
“…In series ranging from 68 to 96 patients, various perfusion parameters, including relative cerebral blood flow (rCBF), relative mean transit time, relative cerebral blood volume (rCBV), and time to peak, have been found to be associated with hemorrhagic transformation. [24][25][26] Given that minor hemorrhagic transformation is common and generally not clinically relevant, 27 we sought to identify the optimal whole-brain CTP parameter for prediction of cerebral parenchymal hematoma (PH) after stroke.…”
Section: Strokementioning
confidence: 99%
“…MRI-based clinical studies of patients with acute stroke treated or not with thrombolysis have shown that very severe reductions of CBV (termed as Very Low CBV) are strongly associated with the risk of PH, [7][8][9] particularly when delayed reperfusion occurs after thrombolysis. 8 Using perfusion CT, the risk of hemorrhagic transformation has been related to a myriad of perfusion measures such as low relative CBV values, 10 low relative CBF values, 11 longer relative MTT or Tmax values, 11,12 and severe hypoperfusion detected in TTP maps. 13 Specifically in patients receiving endovascular reperfusion therapies, reduced pretreatment CBV or CBF values measured with perfusion CT have been associated with poor clinical outcomes, 14 including the risk of development of intracranial hemorrhage.…”
Section: Introductionmentioning
confidence: 99%